Immunotherapy combined with chemotherapy without locoregional radiotherapy in de novo metastatic nasopharyngeal carcinoma: two case reports and a literature review - Gao, Yingna; Shi, Xiaoqiong; He, Jianqiao; Yao, Hui; Yu, Guoning; Zhao, Lin; Ma, Yi; Zheng, Hongliang; Zhu, Minhui; Zhang, Caiyun (Frontiers in Immunology, 2025)
BackgroundThere is no consensus regarding the optimal regimen for de novo metastatic nasopharyngeal carcinoma (dmNPC). Locoregional intensity modulated radiotherapy (LRRT) following palliative chemotherapy (PCT) has been shown to prolong the overall survival (OS) and improve the progression-free survival (PFS) of patients with dmNPC, compared with PCT alone. However, patients with a high tumor burden do not benefit from additional LRRT, which inevitably results in toxicity. Recently, immunotherapy has made great progress in the treatment of recurrent or metastatic NPC (RM-NPC). Compared with PCT alone, programmed death-1(PD-1) inhibitors combined with PCT have shown a promising survival outcome and an acceptable safety profile. Therefore, this treatment strategy is recommended as a first-line therapy for RM-NPC. However, whether dmNPC can be treated with immunochemotherapy alone (without LRRT) remains controversial.Case presentationWe report two cases of dmNPC, both in middle-aged men who mainly presented with epistaxis and systemic pain. Radiological examination with positron emission tomography–computed tomography (PET-CT) and contrast-enhanced magnetic resonance imaging (MRI) showed NPC with multiple systemic lymph node metastases, multiple bone metastases, and liver metastases. Both patients were diagnosed with dmNPC and received pabolizumab in combination with six courses of platinum-based chemotherapy treatment. After complete remission (CR) was achieved, the patients were maintained on pabolizumab alone. No LRRT was used throughout the course of the disease. Pre- and post-treatment levels of plasma Epstein-Barr virus (EBV) DNA were measured, and radiological imaging was performed before and after treatment.ResultsWe achieved good efficacy in these two cases of dmNPC. Both patients exhibited survival benefits (PFS has reached 31 months since diagnosis), and no serious chemotherapy- or immune-related adverse reactions occurred. Treatment-related toxicity from radiotherapy was avoided. Levels of plasma EBV DNA decreased and remained below the minimum detection level consistently after four or five cycles of treatment, with no obvious symptoms of neck muscle fibrosis, throat mucosa dryness, ear congestion, or nasal congestion.ConclusionOur findings suggested that chemotherapy combined with a PD-1 inhibitor without LRRT, followed by sequential immunotherapy as maintenance, can achieve good results in some dmNPC patients. Further validation of our results may be required in large, high-quality prospective clinical studies.